Combining sampling techniques aids monitoring of tropical butterflies. Issue 4 (28th October 2018) - Checa, Maria F.; Donoso, David A.; Rodriguez, Jacqueline; Levy, Elisa; Warren, Andrew; Willmott, Keith
Abstract: We compared the performance of three common techniques for sampling butterflies in order to better understand any bias associated with each method. This information is still scarce for the Neotropics where butterfly diversity reaches a peak. These techniques included use of hand nets, carrion traps with fermented shrimp, and fruit traps with fermented bananas. We examined which taxonomic groups were sampled by each technique and determined the intra‐annual and inter‐annual (two continuous years) differences in the collection of butterflies from each approach. Surveys of butterflies were taken every 2 months, in dry and wet seasons, over a 2‐year period, and were carried out in two forests (one wet and one dry) in western Ecuador. A total of 2289 butterflies of 231 species were collected. Hand‐netting collected the most species (57% and 60% of total species in the dry and the wet forest, respectively), followed by carrion traps (24% and 23%), and then fruit traps (19% and 16%). Methods differed with respect to the butterfly species they collected most frequently. Moreover, each sampling technique resulted in significant differences in species composition across seasons and years. Because our sampling techniques differed in their performance, our study suggests that implementing all the methods together can improve estimates of species diversity and result in more accurate characterisation of butterfly communities. While budget and logistics might constraint the utilisation of multiple techniques, minimally we recommend using both carrion and fruit baits to alleviate the bias of each bait.